Comparative Evaluation of Centesimal and Fifty-Millesimal (LM) Potencies in the Homoeopathic Management of Psoriasis: A Pilot Randomized Controlled Trial - Dr. Amit Nayak; Dr. Heena Rawal; Dr. Poorav Desai; Dr. Rakesh Gohel; Dr. Hina Shah (The Bioscan, 2025)
Background: Psoriasis is a chronic inflammatory dermatosis with significant physical and psychosocial burden. Homoeopathy employs individualised prescribing using different potency scales, most commonly centesimal and fifty-millesimal (LM) potencies. Comparative clinical evidence between these potency scales remains limited. Objective: To compare the clinical effectiveness of individualised homoeopathic treatment using centesimal and LM potencies in patients with psoriasis. Methods: This study was conducted as a pilot randomized controlled trial at the outpatient department of Jawaharlal Nehru Homoeopathic Medical College and Hospital. Ten patients with clinically diagnosed psoriasis were randomly allocated into two parallel groups: LM potency group (n = 5) and centesimal potency group (n = 5). In both groups, remedies were selected on an individualised basis according to classical homoeopathic principles; the potency scale was the only variable. Disease severity was assessed using the Psoriasis Area and Severity Index (PASI) at baseline and after six months. Statistical analysis included paired and independent t-tests. Results: Both groups showed statistically significant reduction in PASI scores from baseline (LM: p = 0.001; centesimal: p = 0.003). The LM potency group demonstrated a greater mean PASI reduction compared to the centesimal group, with a statistically significant between-group difference (p = 0.041). Conclusion: Individualised homoeopathic treatment was associated with significant improvement in psoriasis severity. In this pilot trial, LM potencies demonstrated greater PASI reduction compared to centesimal potencies. Larger randomized trials are warranted to confirm these findings. Trial Design: Pilot randomized controlled trial. Keywords Psoriasis, Individualised homoeopathy, LM potency, Centesimal potency, PASI, Pilot RCT